1995
DOI: 10.1002/bjs.1800820910
|View full text |Cite
|
Sign up to set email alerts
|

Urge incontinence of faeces is a marker of severe external anal sphincter dysfunction

Abstract: A proportion of patients with faecal incontinence experience debilitating urgency of defaecation and urge incontinence. This study prospectively assessed 56 faecally incontinent patients by means of standard interview, physical examination and anorectal physiology. Patients with urge incontinence, when compared with those without urge incontinence, were symptomatically worse, had had more vaginal deliveries and had more bowel actions each day. Physiological tests included anal manometry, anal electrosensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 11 publications
3
20
0
1
Order By: Relevance
“…In accordance with previous studies we found a significant negative relation between internal anal sphincter lesions and resting pressure [56,57], and a significant negative association between external anal sphincter lesions and maximal squeeze pressure [26,27,56,58,59]. The levator ani consists of different muscle components, of which the puborectal muscle is closely aligned to the deep part of the external anal sphincter and forms the upper outer part of the anal sphincter.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previous studies we found a significant negative relation between internal anal sphincter lesions and resting pressure [56,57], and a significant negative association between external anal sphincter lesions and maximal squeeze pressure [26,27,56,58,59]. The levator ani consists of different muscle components, of which the puborectal muscle is closely aligned to the deep part of the external anal sphincter and forms the upper outer part of the anal sphincter.…”
Section: Discussionsupporting
confidence: 91%
“…Nearly all patients with UFI were noted to have abnormal EAS function, irrespective of rectal sensory thresholds, supporting the observation that EAS dysfunction is the major pathophysiological factor in this condition. [5][6][7] In contrast, 50% of patients with RH had evidence of IAS disruption, three times higher than in patients with NS. Although the proportions of patients with a functionally poor IAS (as reflected by reduced anal resting tone) were similar between groups, recording solely maximum resting tone does not reflect ''global'' IAS function.…”
Section: Rectal Sensation and Anal Sphincter Functionmentioning
confidence: 89%
“…4 External anal sphincter (EAS) dysfunction, either secondary to compromised structural integrity, neurological injury, or a combination of both, is recognised as the major cause of UFI. [5][6][7] Nevertheless, patients with an anatomically intact and normal functioning EAS also experience episodes of UFI, 8 indicating that other pathophysiological mechanisms may contribute to symptoms. It is known that alterations in suprasphincteric mechanisms influence continence 9 but their precise role in UFI remains undetermined.…”
mentioning
confidence: 99%
“…In prospective studies, nearly 35% of primiparous women (normal ante partum) showed evidence of sphincter disruption following vaginal delivery (26)(27)(28). Other important risk factors include forceps delivery, prolonged second stage of labor, large birth weight, and occipito-posterior presentation (29)(30)(31). Perineal tears, even when carefully repaired, can be associated with incontinence, and patients may either present immediately or several years following delivery (27).…”
Section: Pathogenic Mechanisms and Etiologymentioning
confidence: 99%